STRATEGI PELAKSANAAN PEMBELAJARAN KOSAKATA BAHASA INGGRIS PADA PESERTA DIDIK USIA DINI DI TK ALIFBA LAMPASEH KOTA BANDA ACEH - Sariakin, Sariakin; Faizah, Cut (LPPM Institut Pendidikan Nusantara Global, 2023)
This research aims: (1) to examine what strategies are used by kindergarten teachers in implementing English vocabulary learning, (2) to examine strategies for implementing English vocabulary learning carried out by teachers in TK Alifba, and (3) to examine how teachers Alifba Kindergarten evaluates the results of the strategy for implementing the English vocabulary learning process. This research was qualitative research because it only describes the situation and condition of the strategy for implementing the English vocabulary learning process in Alifba Kindergarten. Since only one teacher teaches English, the teacher is taken as the research subject and is called the data source. The instruments used to collect data are observation, interviews, and documentation. The data obtained were analyzed with narrative procedures. The results of the study show that in the strategy for implementing the vocabulary learning process, the Alifba Kindergarten teacher prepares the syllabus and teaching materials per lesson package. Teachers use various strategies in implementing the learning process and these strategies include singing, playing roles, and through picture cards. Furthermore, in evaluating the results of the implementation of the teaching and learning process, the teacher evaluates students using one type of test, namely the walking process test. The tests are carried out individually.